Enhancing employee’s contextual performance based on interpersonal skills and creativity - Irvandi Gustari; Widodo Widodo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Employees' performance is incredible impact on the organizations, includes increase organizational effectiveness, productivity, growth, and performance. Therefore, this study focuses on investigating the effect of interpersonal skills on creativity and contextual performance, creativity on contextual performance, and finding the role of creativity in mediating interpersonal skills affects contextual performance. A questionnaire on the Likert scale collected data through the survey methods from 250 employees of companies in Indonesia. Data analysis uses path analysis completed by descriptive and correlational analysis. Data processing was carried out using SPSS 22 and LisRel 8.80.  The results indicated that interpersonal skills significantly affect creativity and contextual performance; creativity significantly affects contextual performance, and interpersonal skills significantly affect contextual performance mediated by creativity. This study confirms a new empirical model regarding the mediating effect of interpersonal skill creativity on employee contextual performance that deserves discussion by researchers and practitioners before being adapted or adopted.